2023
DOI: 10.1109/tnsre.2023.3238764
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Sleep Stage Classification via Neural Architecture Search

Abstract: With the improvement of quality of life, people are more and more concerned about the quality of sleep. The electroencephalogram (EEG)-based sleep stage classification is a good guide for sleep quality and sleep disorders. At this stage, most automatic staging neural networks are designed by human experts, and this process is time-consuming and laborious. In this paper, we propose a novel neural architecture search (NAS) framework based on bilevel optimization approximation for EEG-based sleep stage classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…When in a home-based setting, it is hard to guarantee the high quality of the collected EEG signals due to its sensitivity to environment. The existing mainstream end-toend sleep staging models require both EEG and EOG signals with high qualities to build sleep staging task to achieve good performance [50]. Fortunately, we can collect high-quality EOG signals at home due to their low environmental requirements.…”
Section: Discussionmentioning
confidence: 99%
“…When in a home-based setting, it is hard to guarantee the high quality of the collected EEG signals due to its sensitivity to environment. The existing mainstream end-toend sleep staging models require both EEG and EOG signals with high qualities to build sleep staging task to achieve good performance [50]. Fortunately, we can collect high-quality EOG signals at home due to their low environmental requirements.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no universal approach to guide the design of deep learning models for arbitrary classification tasks, given the diversity in layer modules and optimization strategies. Furthermore, besides the experiments presented in this study, there are various types of datasets available for further validation [30], [31],…”
Section: Repeat Relu-lcn Leaky-lcnmentioning
confidence: 99%
“…NAS has demonstrated advancements in improving model performance across various applications, such as image processing [24], [25], semantic segmentation [26], [27], and object detection [28], [29]. Recent research also explores the use of NAS for healthcare applications, such as electroencephalography (EEG) data processing [30], muscle fatigue detection [31], cardiac abnormality diagnosis [32], and heartbeat classification [33]. Moreover, an NAS was developed by leveraging k-fold cross-validation, and the deep learning model was evaluated on data from the UCR archive [34].…”
mentioning
confidence: 99%
“…Phan et al (2021) [17] also compared the performances of CNNs, recurrent neural networks (RNNs), and transformer networks on a large-scale dataset of PSG recordings, and found that the transformer networks outperformed the CNNs and RNNs in accuracy and generalization to unseen data. Kong et al (2023) [18] proposed a novel neural architecture search (NAS) search framework for EEG-based sleep staging. It optimized the model by search-space Jinji and search-space regularization and sharing parameters between units.…”
Section: Automatic Sleep Staging Algorithm Modelmentioning
confidence: 99%